(untitled) (International Journal of Phytopharmacy, 2017)
The phytochemical analysis of four species of medicinal plants from district Saharanpur was done. The plants were Wrightia coccinea , Wrightia tinctoria , Wrightia mollissima and Wrightia tomentosa , members of the genus Wrightia (Family: Apocynaceae).Qualitative phytochemical analysis of these plants confirms the presence of various phytochemicals like alkaloids, flavonoids and terpenoid. The presence of these phytochemicals can be correlated with medicinal potential of these plants.